PENGARUH TOTAL QUALITY MANAGEMENT (TQM), GAYA KEPEMIMPINAN, KEDISIPLINAN KERJA DAN FUNGSI MENTORING TERHADAP KINERJA KARYAWAN PT. KEMAKMURAN BERKAH TIMBER SAMARINDA - Tipung, Dionesia Deska (EKONOMIA, 2018)
To be able improved Performance Employees in a company or organization, hence required by factors able to improve Performance itself. As for the factors is Totalizeing Quality Management, Style Leadership, Job Discipline and Function of Mentoring.This Formula research internal issue is